Pengaruh Brand Image Dan Kualitas Produk Terhadap Keputusan Pembelian Melalui Minat Beli Pada Pelanggan Mitsubishi Xpander Di PT Dipo Amplas - Satria Mirsya Affandy Nasution; Rifqi Ahmad Naufal (CERED Indonesia Institute, 2026)
both directly and indirectly through job satisfaction as an intervening variable. This study is an associative study with a quantitative method approach. The study population was employees of PT Kereta Api Indonesia Persero Division I North Sumatra Region with a total of 94 respondents. Data were collected through questionnaires and processed using SEM-PLS (Structural Equation Modeling - Partial Least Square). The results of the study indicate that work discipline has a positive and significant effect on employee performance while supervision does not have a significant effect on employee performance. Work discipline does not have a significant effect on job satisfaction, while supervision has a positive and significant effect on job satisfaction. Job satisfaction does not have a significant effect on employee performance. In addition, work discipline on employee performance through job satisfaction does not have a significant effect, and supervision on employee performance through job satisfaction also does not have a significant effect. The results of this study indicate that work discipline has a direct role in improving employee performance, while supervision has a greater effect on job satisfaction. However, job satisfaction does not function as a mediating variable in the influence of work discipline and supervision on employee performance.